Modelagem hidrogeológica de fluxo e transporte advectivo na bacia do córrego do Engenho Nogueira no campus Pampulha da UFMG, Belo Horizonte - MG - Laila Garcia Maia Goncalves (2015)
This study was conducted in part of the Engenho Nogueira creek basin, comprising areas of campus Pampulha/UFMG and Centro de Desenvolvimento da Tecnologia Nuclear in Belo Horizonte, MG. The objectives of this study were the construction and calibration of agroundwater flow numerical model and its application in particles advective transport assessment. Secondary data generated over 15 years were synthesized into a permanent numerical modeling. In addition, protection zones were stated for wells currently in operation and for those that are under consideration of activation. Visual MODFLOW software, version 2011.1, and its particle transport module, MODPATH, were the tools used to access such objectives. Study area lithotypes are part of the Belo Horizonte Complex, locally represented by gneisses cut by diabase dikes and quartz veins, forming a fissure aquifer system. Sedimentary covers produced by weathering, with thicknesses ranging from 45 to 50 meters, are represented by residual soils and sandy-clay to clayey-sand colluvium, and clayey-sand alluvial deposits with plastic organic clay lenses, which is situated in the region near to the stream thalweg. This sedimentary cover constitutes the granular aquifer system with close hydraulic connection to the bottom fissural aquifer. Five hydrogeological units were divided and five recharging zones were defined in the study area ranging from 100 to 400 mm/year according to land use, material texture and altitudes. Flows numerical modeling proved compatible with the conceptual model designed for the area, and indicated lack of information on the aquifer, observation wells and defined boundary conditions. The model error was small with a NRMS of 4.354% and mass balance of 0.12%. Sensitivity analysis indicated that the model was sensitive to recharge and mostly to hydraulic conductivity of hydrogeological units set for granular aquifer system, emphasizing the importance of detail used. With particles advective transport, wells protection zones were stated in years 1, 2, 5, 20 and 30 after particles exposure in the saturated zone, and found that contaminated areas distant to the wells can affect pumped water quality to tens of meters away over time. This work contributed with knowledge to be considered in the UFMG / CDTN aquifer systems management and qualitative and quantitative protection plans.